Effectiveness of the program on the level of coordination skills of older school aged hockey players - Chovanova, E.; Chovan, L (Acta Universitatis Matthiae Belii, Physical Education and Sport, 2012)
Based on our research implemented at the sample of 44 subjects of 14 years old sport population of east Slovakia region we reached the following conclusions: Identified by a set of knowledge reached and published we notice that we reached the aim and hypothesis was verified. Trainers can use conclusions obtained in their training process for the age group of older schol age players. We are aware that knowledge reached from research of coordination skills of 14 - years aged sport population of eastern Slovakia region cannot be fully generalized. It is influenced by: regionality of research, low - volume of the units. That`s why our conclusions can not claim universal validity.